Transport actif de Na+ et K+ à travers les épithéliums chez la truite arc-en-ciel (salmo gairdneri irideus gibbons) acclimatée en eau marine - Crăciun, V.; Crăciun, Margareta; Neacșu, Ion; Ioniță, Reveica (Cercetări Marine - Recherches Marines, 2026)
The results on the activity of Na+ and K+ dependent ATP-ase of the epithelia of the Black Sea adapted rainbow trout (Salmo gairdneri irideus) in comparison with the fresh water maintained rainbow trout are presented. In these conditions the active transport of Na+ and K+ through gills, intestine and kidney is reduced at the marine adapted one.